Perforated giant mycotic aneurysm of mitral valve in a drug‐addicted young man: Rare complication of infective endocarditis. Issue 1 (26th November 2017) - Lavanco, Vincenzo; Curzi, Mirko; Giustiniano, Enrico; Raspante, Donatella; Di Lisi, Daniela; Bragato, Renato Maria
Abstract : Infective endocarditis (IE) affects patients at high clinical risk and may present as an acute and rapidly progressive, subacute or chronic infection. Transthoracic and transesophageal echocardiography represent the key diagnostic method in IE diagnosis. In particular, three‐dimensional transesophageal echocardiography represents the imaging technique that allows to establish with adequate accuracy dimensions, shape, and localization of endocarditis vegetations. In our case, we show a huge vermiform mycotic aneurysm in an immunodeficient young drug‐addicted man with severe mitral valve regurgitation and the additive value of three‐dimensional transesophageal echocardiography in this specific clinical setting.